Electrochemical Detection of Environmental Pollutants Based on Graphene Derivatives: A Review - Kumunda, Coster; Adekunle, Abolanle S.; Mamba, Bhekie B.; Hlongwa, Ntuthuko W.; Nkambule, Thabo T. I. (Frontiers in Materials, 2021)
Population-driven socioeconomic urban expansion, industrialization and intensified modern agricultural practices are interlinked to environmental challenges which induce harmful repercussions on the health of human beings. Consequently, these challenges have culminated in compromised water quality due to pollution by toxic, persistent and bioaccumulative heavy metal ions, pesticides, and emerging pollutants. Most pollutants cause severe health dilemma including impairment of vital body organs like lungs, liver, kidneys, reproductive and nervous systems. Besides, some organic contaminants interfere with natural enzyme and hormonal functioning such as the endocrine system. Considering the detrimental impact of pollutants, their detection in different media including water is paramount. Notably, electrochemical techniques are more appealing owing to their facileness, sensitivity, portability, the potential for being used instantaneously, in situ and onsite comparative to conventional methods. Electrochemical sensing utilizing graphene derived nanocomposites have become attractive based on mechanical strength, electric conduction, and huge surface area to volume ratio of graphene. Apart from that, graphene-based materials are functionalisable owing to the prevalence of oxygen-rich entities. Thus, they are amenable for the incorporation of different components for modifying electrodes. Ultimately, combinational synergistic aftermaths in electrochemical sensor behaviour are being realized following functionalization and electrode modification with nanocomposites. This review summarizes graphene and its derivatives synthesis pathways. Besides that, the review describes the functionalization of graphene derived materials exploiting properties of metal (oxides) nanoparticles, conducting polymers, organic or inorganic materials, and other carbon materials like carbon nanotubes. Furthermore, the review evaluates the recent electrochemical detection of heavy metal ions, pesticides and emerging pollutants founded on hybridized graphene. For natural organic matter, the absence of reports on their sensing based on functionalized graphene derivatives is highlighted. In reckoning, current challenges related to graphene applicability, envisaged opportunities and future perspectives are outlined.